Who We Seek and What We Eat? Sources of Food Choice Inspirations and Their Associations with Adult Dietary Patterns before and during the COVID-19 Lockdown in New Zealand - Roy R; Gontijo de Castro T; Haszard J; Egli V; Te Morenga L; Teunissen L; Decorte P; Cuykx I; De Backer C; Gerritsen S (MDPI (Basel, Switzerland), 2021)
Research shows the shaping of food choices often occurs at home, with the family widely recognised as significant in food decisions. However, in this digital age, our eating habits and decision-making processes are also determined by smartphone apps, celebrity chefs, and social media. The 'COVID Kai Survey' online questionnaire assessed cooking and shopping behaviours among New Zealanders during the 2020 COVID-19 'lockdown' using a cross-sectional study design. This paper examines how sources of food choice inspirations (cooking-related advice and the reasons for recipe selection) are related to dietary patterns before and during the lockdown. Of the 2977 participants, those influenced by nutrition and health experts (50.9% before; 53.9% during the lockdown) scored higher for the healthy dietary pattern. Participants influenced by family and friends (35% before; 29% during the lockdown) had significantly higher scores for the healthy and the meat dietary patterns, whereas participants influenced by celebrity cooks (3.8% before; 5.2% during the lockdown) had significantly higher scores in the meat dietary pattern. There was no evidence that associations differed before and during the lockdown. The lockdown was related to modified food choice inspiration sources, notably an increase in 'comforting' recipes as a reason for recipe selection (75.8%), associated with higher scoring in the unhealthy dietary pattern during the lockdown. The lockdown in New Zealand saw an average decrease in nutritional quality of diets in the 'COVID Kai Survey', which could be partly explained by changes in food choice inspiration sources.
Keywords: COVID-19; nutrition; dietary patterns; feeding behaviours; food influence; food preferences; cooking; surveys and questionnaires; social media; New Zealand; 0908 Food Sciences; 1111 Nutrition and Dietetics